(untitled) (Medical Forum Monthly, 2024)
Objective: To know the frequency of Significant Structural Heart Disease in Neonates Presenting with Cardiac Murmer. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Paediatric Department, Sheikh Zayed Hospital Lahore from July 2013 to December 2013. Materials and Methods: Seventy five (75) neonates with murmur collected from Nursery, Postnatal Gynae Ward and Out-Patient Department of Shaikh Zayed Hospital .The information was recorded in a pre-formed Performa, Data was analyzed using statistical package SPSS 12. Results: Echocardiography confirmed murmurs in 65 neonates due to significant structural heart disease and remaining 10 murmurs were functional. Regarding frequencies of different heart defects VSDs were 43 (57.3%), ASDs 13 (17.3%), PDAs 6 (8%) and PS, ASD + PDA and VSD + ASD 1 (1.3%) each. Conclusion: The clinician should have high index of suspicion regarding congenital heart disease especially in neonates presenting with murmur. Having missed, a large number of neonates with significant congenital heart disease present late when they actually become in-operatable resulting in disability or even death of the neonate.